Histological and Immunological Evaluation of the Osteogenic Effects of Compact Bone-Delivered Stem Cell on Spongiosis Bone in the Rat Zygomatic Arch Defect Model - AKKOÇ, TUNÇ (My University, 2023)
BACKGROUND: In stem cell applications, apart from bone marrow and adipose tissue, compact bone is also used as an alternative. However, studies on this subject are limited. In our study, we investigated the effect of stem cell derived from compact bone on rat zygomatic arch defect. METHODS: Fifteen rats were included in the study. Five rats were killed to obtain stem cells before the experiment. The rats were divided into 2 groups with 5 rats each. In group 1, compact bone-derived stem cell was applied. In group 2, adipose tissue-derived stem cell was applied. Right zygomatic arch defect was created in rats in both groups. Zygomatic bones were decellularized by cryosurgery. Stem cells were transferred to zygomatic bones. The number of stem cells, stem cell differentiation, and superficial markers obtained from the groups were examined. Histologically, cell structure, osteocyte count and osteopontin scores, elemental composition of the groups, percentages of resemblance to intact bone, osteocytes numbers, and cells were examined by electron microscopy of the bones in the groups after killing. RESULTS: The number of stem cells administered to the groups was 5 × 107 and 3.2 × 107 for group 1 and group 2, respectively (P > 0.05). Histologically, the morphology of the cells in group 1 was found to be healthier than group 2. The number of osteocytes was 97.56 ± 15.4 and 132.93 ± 10.8 in group 1 and group 2, respectively (P 0.05). Osteocyte counts were 10.7 ± 2.8 and 6.1 ± 1.2 in group 1 and group 2, respectively (P 0.05). CONCLUSION: Stem cells obtained from compact bone gave positive results in zygomatic arch defect. This method can also be used as an alternative in stem cell applications.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery